Resonances arising from Sheltering in the Family Dynamics of Brazilian Women in situations of Violence - Krenkel, Scheila; Universidade Federal de Santa Catarina (2016)
This study aimed to analyze the repercussions of sheltering in the family dynamics of women in situations of violence. This is a qualitative study in which 12 Brazilian women who were given shelter due to have suffered from violence were interviewed. The data organization and analysis was supported by the Grounded Theory, with the help of Atlas.ti software. Before being in the shelter, the study revealed the hardening of family relations and breaking of affectional bonds as well feelings of anxiety, depression, shame, fear and humiliation. Their permanence in the shelter helped the women to create strategies of coping with violence, which in turn, contributed to their reintegration in society as well as the recovery of their dignity and citizenship.